Silagem de resíduo úmido de fécula de mandioca na alimentação de ruminantes - Gonçalves, João Arlindo Gouveia (2011)
The aim of this study was to evaluate the in vivo digestibility of the silage residue wet cassava starch (SRWCS) replacing corn in diets and quality during the ensiling process. The corn was replaced in the diet of sheep by SRWCS in proportions of 0%, 25%, 50%, 75% and 100%; and for the evaluation of SRWCS used two treatments, in natura and one with material pre dry. We used five castrated male sheep were cannulated distributed in a 5x5 Latin square design (five treatments and five replicates) within 14 days of adaptation and 7 days for data collection at 105 days of experimental period. For the assessment of SRWCS the material was ensiled in experimental silos of Chlorides Polyvinyl. The moist residue of cassava starch can be ensiled and fresh or pre-dried with no differences (P> 0.05) for crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), hemicellulose, lignin and cellulose in the material fresh and pre-dried. There was no difference in the amounts of dry matter (DM), organic matter (OM), CP, NDF, lignin, ether extract (EE) during the days of ensiling. There was high correlation of pH with the growth of enterobacteria, lactobacilli, Clostridium, fungi and yeasts. The SRWCS can replace corn in the diet of sheep, not to change the digestibility of dry matter, organic matter, crude protein, ether extract, neutral detergent fiber, acid detergent fiber and total carbohydrates of the diet